The role of managerial work in market performance: A monopoly model with team production - Andreas Hildenbrand; Mihael Duran (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
A monopolist is treated as a nexus of contracts with team production. It has one ownermanager. The owner-manager is the employer of two employees. A team production problem is present if the employer is a managerial lemon. If the team production problem is solved, the employer is a managerial hotshot. Both a managerial hotshot and a managerial lemon are found to make profit. Managerial slack can therefore exist in our monopoly market. In the case of a managerial lemon, the profit level is lower. However, the employees' utility level is higher. Whereas the employer has an incentive to improve management capability in principle, the employees have an incentive to keep management capability low. Moreover, the cost of improving management capability may be prohibitively high. Managerial slack can therefore persist. The predicted behavior of the monopolist is grounded in individual behavior under the assumption of utility maximization.
Keywords: C7; D2; D4; L1; L2; 330; firm organization; market structure; property rights